Disain dan Validitas E-Modul Interaktif Berbasis Konflik Kognitif untuk Remediasi Miskonsepsi Siswa pada Konsep Gaya - Viki Pratama; Sonia Fitri Anggraini; Hilman Yusri; Fatni Mufit (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Student misconceptions occur because students build their own concepts from their own environment without the help of experts, therefore, students' initial knowledge that is not the same as expert opinion is what causes misconceptions. This study aims to produce an interactive conflict-based cognitive e-module to remediate misconceptions and improve students' understanding of concepts about force. This type of research is design or development research using the Plomp model, with 3 phases, namely; (1) preliminary research, (2) development phase and (3) assessment phase. This research is limited to the expert review development phase. The preliminary research was conducted by reviewing 5 journals about the problems of students' misconceptions on the concept of force. At the development phase, e-module design, self-evaluation, and expert review of the e-module prototype are carried out. The data were obtained from the self-evaluation assessment sheet by three researchers and the validation sheet by three physics lecturers. Based on the preliminary research, it was found that there were problems in understanding the concept of students in the material of force. Therefore, a cognitive conflict-based emodule was designed that could improve students' conceptual understanding. The self-evaluation results of the emodule design showed that the e-module design was in the very good category with an average of 93.4. The results of the expert's study showed that the e-module design was in a very valid category with an average of 85.6.